High capacity performance of NiCo2O4 nanostructures as a binder‐free anode material for lithium‐ion batteries. (28th March 2021) - Kakarla, Ashok Kumar; Narsimulu, D.; Yu, Jae Su
Summary: Recently, binder‐free nanostructured materials provide a great opportunity for advanced lithium‐ion batteries (LIBs) owing to their improved electrical conductivity with good porous structure. NiCo2 O4 (NCO) nanostructures were successfully deposited on copper foam (CF) substrate to form porous three‐dimensional (3D) NCO@CF hybrid structures via a simple solvothermal synthesis, followed by further heat treatment at 300°C (designated as NCO@CF‐300) and 400°C (NCO@CF‐400). The as‐prepared samples revealed distinctly mixed morphologies of 2D nanosphere and nanowire‐like structures, tuned by the further heat treatment. Both the electrodes could be explored as a binder‐free anode for next‐generation LIBs. It is demonstrated that the good integration of 2D morphology of NCO with 3D architectured CF has a significant effect on its electrochemical results. For the first cycle, binder‐free NCO@CF‐300 and NCO@CF‐400 electrodes delivered the discharge capacity values of 1946 and 2637 mA h g −1, respectively, at 500 mA g −1 . Moreover, the NCO@CF‐300 electrode exhibited stable reversible capacity and good rate capability. From these results, the growth of NCO nanostructures on the CF can be suggested as a potential anode material for high‐performance Li‐ion batteries. Abstract : Porous binder‐free NiCo2 O4 nanosphere and nanowire‐like electrode exhibits remarkable electrochemical performances as an anode material for long‐lifetime lithium‐ion batteries.